(untitled) (International Journal of Innovative Technologies in Economy, 2024)
With debt policy as a moderating factor, this study attempts to examine the effect of dividend policy and return on equity on stock prices in property and real estate sub-sector companies listed on the Indonesia Stock Exchange. Ten companies became the sample size for this study, which used purposive sampling technique. The data analysis technique in this study is multiple regression analysis technique using MRA with the help of SPSS 25.0 program. The results of the study explain that dividend policy affects stock prices while return on equity has no effect on stock prices. Debt policy is unable to moderate the effect of dividend policy and return on equity on stock prices in property and real estate sub-sector companies for the period 2020-2022.